Role of Contrast-Enhanced Voiding Urosonography in the Evaluation of Renal Transplant Reflux – Comparison with Voiding Cystourethrography and a New Classification - Drudi, Francesco Maria; Angelini, Flavia; Bertolotto, Michele; Granata, Antonio; Di Pierro, Giovanni Battista; Lai, Quirino; D'Ermo, Giuseppe; Pretagostini, Renzo; Cantisani, Vito (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
Vesicoureteral reflux (VUR) is a common urological complication in renal transplant patients. The aim of this study is to evaluate the performance of contrast-enhanced voiding urosonography (CEvUS) in the diagnosis and classification of reflux into the renal allograft, to evaluate and classify VUR into the allograft using voiding cystourethrography (VCUG) and CEvUS, to compare the two methods, and to propose a new classification of reflux into the allograft based on CEvUS and VCUG assessment, in line with the international reflux grading system.Materials and Methods From January 2017 to July 2019, 84 kidney transplant patients were enrolled. All patients underwent VCUG and CEvUS.Results In 76 cases there was agreement between VCUG and CEvUS (90 %) (Kappa = 0.7). The sensitivity of CEvUS using VCUG as the gold standard was 90 %, and the specificity was 92 %. Of the 7 cases diagnosed by VCUG and not by CEvUS, 6 were grade 1 and 1 was grade 2.Conclusion Transplant patients with reflux symptoms should undergo CEvUS. If the outcome is negative, VCUG should be performed. The classification that we propose is better suited to describe VUR in transplant patients, because it is simpler and takes into account whether reflux occurs not only during urination but also when the bladder is relaxed.
Keywords: transplanted kidney; vesicoureteral reflux; CEvUS; VCUG; urinary tract